The Usefulness of Clinical and Laboratory Parameters for Predicting Severity of Dehydration in Children with Acute Gastroenteritis - Hoxha, Teuta Faik (Med Arch, 2014)
BACKGROUND: An accurate assessment of the degree of dehydration in infants and children is important for proper decision-making and treatment. This emphasizes the need for laboratory tests to improve the accuracy of clinical assessment of dehydration. The aim of this study was to assess the relationship between clinical and laboratory parameters in the assessment of dehydration. METHODS: We evaluated prospectively 200 children aged 1 month to 5 years who presented with diarrhea, vomiting or both. Dehydration assessment was done following a known clinical scheme. RESULTS: We enrolled in the study 200 children (57.5% were male). The mean age was 15.62±9.03 months, with more than half those studied being under 24 months old. Overall, 46.5% (93) had mild dehydration, 34% (68) had moderate dehydration, 5.5% (11) had severe dehydration whereas, 14% (28) had no dehydration. Patients historical clinical variables in all dehydration groups did not differ significantly regarding age, sex, fever, frequency of vomiting, duration of diarrhea and vomiting, while there was a trend toward severe dehydration in children with more frequent diarrhea (p=0.004). Serum urea and creatinine cannot discriminate between mild and moderate dehydration but they showed a good specificity for severe dehydration of 99% and 100% respectively. Serum bicarbonates and base excess decreased significantly with a degree of dehydration and can discriminate between all dehydration groups (P<0.001). CONCLUSION: Blood gases were useful to diagnose the degree of dehydration status among children presenting with acute gastroenteritis. Serum urea and creatinine were the most specific tests for severe dehydration diagnosis. Historical clinical patterns apart from frequency of diarrhea did not correlate with dehydration status. Further studies are needed to validate our results.